Enhancing the insight into Czech railway level crossings' safety performance. Issue 1 (2nd January 2020) - Ambros, J.; Perůtka, J.; Skládaný, P.; Tučka, P.
ABSTRACT: Railway level crossings (RLCs) are critical elements of both railway and road networks, where accidents mostly result in severe and fatal injuries. In the Czech Republic, most accidents occur on RLCs with flashing lights only. In order to provide insight into safety performance of this RLC category, specific risk factors need to be identified and their overall safety impact quantified. In this regards, the paper describes the application of a multivariate assessment, based on disaggregated safety performance function, developed on a level of sight triangles. The results proved the safety impacts of traffic volumes, as well as speeding and individual sight distances. In addition, this relationship may change based on a distance from RLC: while approaching sight distances were associated with reduction of accident frequency, the opposite trend was found for stopping sight distances. Next, RLC inconspicuousness and potential short storage space were found to be influential risk factors.